APLIKASI TOTAL QUALITY MANAGEMENT (TQM) DI MADRASAH IBTIDAIYAH NEGERI (MIN) PURWOKERTO - sumiarti sumiarti (IAIN Purwokerto, 2017)
Abstract : The Total Quality Management (TQM) application in MIN Purwokerto has met the TQM criteria, i.e. continuous improvement and concrete actions to make changes towards improving the quality of education As Sallis said that TQM application in education has characteristics: (1) Continuous improvement, (2) Kaizen, (3)Changing cultures, (4) The upside-down organization, (5) Keeping close to the customers, (6) Internal customers, (7) Internal Marketing, (8) Professionalism, (9) The Quality of Learning. Keyword : Application, TQM, Islamic Elementary School.